Bioremediation of chromium complex dyes and treatment of sludge generated during the process. (April 2017) - Ghosh, Arpita; Dastidar, Manisha Ghosh; Sreekrishnan, T.R.
Abstract: Bioremediation of chromium complex dyes in synthetic solutions and actual effluent was performed using growing Aspergillus tamarii in batch and continuous bioreactors. Maximum removal of color (90.00 ± 0.20 and 74.00 ± 0.10%) and chromium (94.00 ± 0.10 and 77.50 ± 0.10%) was obtained from synthetic solutions (100 mg/L) of acid brown 45 and acid blue 158 dyes, respectively in batch mode. Optimization of process parameters such as initial concentration of dye, pH and time was performed using response surface methodology (RSM). Biosorption, bioaccumulation and biodegradation of the dyes during bioremediation were supported by TEM and GC-MS analyses. Maximum removal of color (64.50 ± 0.10 and 45.00 ± 0.10%) and chromium (67.00 ± 0.10 and 49.00 ± 0.10%) was obtained at 220 h HRT using solutions (100 mg/L) of acid brown 45 and acid blue 158 dyes, respectively in continuous mode. The removal of color (86.00 ± 0.10 and 65.00 ± 0.20%) and chromium (100.00 ± 0.10 and 81.00 ± 0.10%) was observed in batch and continuous modes, respectively using actual effluent. The lower removal values were obtained using desorbed and dead biomass as compared to actively growing biomass. Phytotoxicity test was conducted using seeds of Cicer arietinum to examine the toxic effect of dye solution before and after bioremediation. Anaerobic digestion of residues (after bioremediation of dyes) indicated maximum methane production of 41.00 ± 0.20% on 16th day of operation. Graphical abstract: Highlights: Bioremediation of chromium complex dyes and effluent was conducted using Aspergillus tamarii in batch and continuous modes. Phytotoxicity test of the dye solution (before and after bioremediation) was performed using the seeds of Cicer arietinum. Desorption of the biomass after bioremediation and reuse of the biomass for dye removal were performed. Study of the mechanism for bioremediation was performed using EDX, TEM and GC-MS analyses. Treatment of generated sludge during bioremediation was conducted through anaerobic digestion and incineration.